THE ROLE OF THE DEFENCE EDUCATION SYSTEM IN MONGOLIA’S NATIONAL RESILIENCE: A SMALL-STATE SECURITY POLICY ANALYSIS - Bayartogtokh, Nergui; Enkhtaivan, Dorjderem (International Journal of Innovative Technologies in Social Science, 2026)
This article aims to analyze the role of the defence education system in Mongolia’s national resilience within the framework of small-state security policy. The contemporary security environment is no longer defined solely by traditional military threats and armed conflicts. Rather, it is increasingly shaped by multidimensional challenges such as information influence, cyber risks, social fragmentation, economic vulnerability, disasters, pandemics, psychological pressure, and insufficient civic preparedness. Under these conditions, national defence capability must no longer be assessed only through the structure of the Armed Forces, weaponry, professional military training, and mobilization reserves. It must also be measured through citizens’ security awareness, civil protection knowledge, information resilience, patriotic formation, social cohesion, and whole-of-society participation.As a small state located between two great powers, with relatively limited demographic, economic, and material defence resources, Mongolia must strengthen its national security not only through military force but also through citizens’ knowledge, participation, values, psychological preparedness, and societal resilience. In this context, defence education is a strategically significant system situated at the intersection of national security policy, education policy, civil-military relations, whole-of-society defence, and national resilience.The study employs document analysis, comparative policy analysis, theoretical synthesis, and a Mongolian case study approach. The article examines the concept of defence education, its legal foundations, the current situation in Mongolia, international experience, and its policy linkage with national resilience. It proposes a “national resilience-based whole-of-society defence education model.” The findings suggest that Mongolia has established certain legal and policy foundations for defence education. However, an independent regulatory framework, unified curriculum standards, inter-institutional coordination, teacher and trainer preparation, and monitoring and evaluation mechanisms remain insufficiently developed.